Psychometric evaluation of the Negative Religious Coping (NRC) Scale of the Brief RCOPE in the Czech environment - Janu, Anna (Mental health, religion & culture, 2019)
The Negative Religious Coping (NRC) Subscale is a part of the Brief RCOPE Scale, but can also be used separatelly. It is a brief measure assessing negative religous coping. The aim of this study was to psychometrically evaluate the NRC in Czech conditions. The NRC was administered to 531 religious respondents (25.5 ± 3.4 years, 43.5% male). Negative religious coping and religiosity, together with basic sociodemographic information, were measured. The non-parametric comparison of different sociodemographic groups showed no differences between genders and almost no differences among the age groups. Significantly lower NRC scores were obtained by widows/widowers. The Czech version of the NRC showed a coherent one-dimensional factor structure and high reliability, with Cronbach’s α = .84 (95% CI .83-.85) and McDonald’s ωt = .90. Our findings indicate that the Czech version of the NRC scale may reliably assess religious coping. This instrument might be useful both for research and clinical praxis.